The Breaking of the Square: Late Victorian Representations of Anglo-Sudanese Warfare - Luisa Villa (Cahiers Victoriens et Edouardiens)
Among the areas affected by the late nineteenth century “scramble for Africa”, the Sudan repeatedly drew the attention of the British public. Though mostly arid, inaccessible, and scarcely attractive from a purely economic point of view, it became a crucial concern for the British executive, as well as a focus of popular anxieties relating to British military prowess (or lack thereof). From the early 1880s (with the rise of the Mahdi, the disastrous defeat of General Hicks at Shaykan, the siege of Khartoum and its fall) to the late 1890s (with the slow advance of Kitchener’s army through the desert and along the Nile culminating in the battle of Omdurman), the military operations conducted in the Sudan not only fuelled a lively public debate, but provided exciting material for literature and popular entertainment. Indeed, with its austere desert landscape, its immemorial river and its warlike populations, the Sudan was marketed to the general public as the site for the perfect martial adventure. Working within this context, the article focuses on the representation of Anglo-Sudanese warfare, drawing on fiction and poetry, as well as on reportage and articles published in magazines. Its focus is the topical battle-scene known as “the breaking of the square”. The analysis elicits reflections on the construction of normative masculinity (with its emphasis on disciplined aggressiveness), on the perception of modern technology (which often made victory over native fighters alarmingly easy and hardly honorable), on the “uses” of violence and on the dynamics of “Imperialist nostalgia” (as the anthropologist Rosaldo dubbed it), i.e. the coloniser’s own regret at the inevitable destruction of native societies brought about by the process of compulsory modernization.